2021
DOI: 10.1177/07487304211031206
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock, the Brain, and COVID-19: The Cases of Olfaction and the Timing of Sleep

Abstract: Daily rhythms of behavior and neurophysiology are integral to the circadian clocks of all animals. Examples of circadian clock regulation in the human brain include daily rhythms in sleep-wake, cognitive function, olfactory sensitivity, and risk for ischemic stroke, all of which overlap with symptoms displayed by many COVID-19 patients. Motivated by the relatively unexplored, yet pervasive, overlap between circadian functions and COVID-19 neurological symptoms, this perspective piece uses daily variations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Another study using actigraphy found that patients with severe COVID-19 symptoms, including those with severe respiratory symptoms and those requiring Intensive Care Unit (ICU) displayed lower sleep efficiency, higher immobility time, and higher fragmentation index compared to those with mild symptoms and who do not require ICU care ( 55 ). Actigraphy may not be the gold standard for evaluating sleep, but it is simple to implement and could be sufficient for identifying changes in sleep schedules that would indicate disturbances of the circadian clock ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study using actigraphy found that patients with severe COVID-19 symptoms, including those with severe respiratory symptoms and those requiring Intensive Care Unit (ICU) displayed lower sleep efficiency, higher immobility time, and higher fragmentation index compared to those with mild symptoms and who do not require ICU care ( 55 ). Actigraphy may not be the gold standard for evaluating sleep, but it is simple to implement and could be sufficient for identifying changes in sleep schedules that would indicate disturbances of the circadian clock ( 56 ).…”
Section: Discussionmentioning
confidence: 99%